2007
DOI: 10.1016/j.cellbi.2007.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine inhibits primary CD4+ T‐cell proliferation via apoptosis

Abstract: Sinomenine is an active component isolated from Sinomenium acutum and is widely used as an immunosuppressive drug for treating autoimmune diseases. CD4(+) T-cell population plays a key role in adaptive immune response and is related to some autoimmune diseases. In this study, we investigated the possible immunosuppressive effect of sinomenine on CD4(+) T cells and its underlying mechanism. Our data demonstrated that sinomenine remarkably suppressed the proliferation of CD4(+) T cells, blocked the cell cycle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The topical application of SIN in the treatment of rheumatoid arthritis has potential advantages (Zheng et al, 2007). It has previously been demonstrated that SIN exhibited a wide range of pharmacological actions including anti-inflammatory, anti-rheumatic, immunosuppressive, analgesic and antiarrhythmic effects (Shu et al, 2007;Teng et al, 2012;Song et al, 2013). And there are many other researches indicate that SIN has many pharmacological characters such as inducing apoptosis and anti-angiogenesis effect what has been treated as means of treating colon carcinoma (Kok et al, 2005;Ju et al, 2010;Chen et al, 2011).…”
Section: Suppressive Effect Of Sinomenine Combined With 5-fluorouracimentioning
confidence: 99%
See 2 more Smart Citations
“…The topical application of SIN in the treatment of rheumatoid arthritis has potential advantages (Zheng et al, 2007). It has previously been demonstrated that SIN exhibited a wide range of pharmacological actions including anti-inflammatory, anti-rheumatic, immunosuppressive, analgesic and antiarrhythmic effects (Shu et al, 2007;Teng et al, 2012;Song et al, 2013). And there are many other researches indicate that SIN has many pharmacological characters such as inducing apoptosis and anti-angiogenesis effect what has been treated as means of treating colon carcinoma (Kok et al, 2005;Ju et al, 2010;Chen et al, 2011).…”
Section: Suppressive Effect Of Sinomenine Combined With 5-fluorouracimentioning
confidence: 99%
“…Extracted from the Chinese medicinal plant, Sinomenium acutum, SIN has been utilized to treat rheumatoid arthritis (RA) in China for over 2000 years. Previous reports have demonstrated a wide range of pharmacological actions including anti-inflammatory, anti-rheumatic, immunosuppressive, analgesic and antiarrhythmic effects (Shu et al, 2007;Teng et al, 2012;Song et al, 2013). But its potential value of anti-tumor by inhibiting proliferation and induced apoptosis was recognized in recent years (He et al, 2005;Li et al, 2008).…”
Section: Evaluation Of Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesized that SIN could also inhibit bone resorption and the survival of mature osteoclasts by inducing osteoclast apoptosis. Recently, SIN has been shown to modulate caspase activation to induce apoptosis [9,12,13] . However, there is currently no report about the effect of SIN on the apoptosis of osteoclasts.…”
mentioning
confidence: 99%
“…We found that SIN can significantly inhibit www.nature.com/aps He LG et al Acta Pharmacologica Sinica npg osteoclastogenesis and resorptive activity in vitro and in vivo (data not shown). Notably, SIN is known to induce apoptosis in various types of cells [9][10][11][12][13][14] . Therefore, we hypothesized that SIN could also inhibit bone resorption and the survival of mature osteoclasts by inducing osteoclast apoptosis.…”
mentioning
confidence: 99%